Integrating Agronomic Practices and Plant Physiological Strategies to Enhance Fruit Yield under Climate Stress Conditions - , Baibhabi Bindia Nayak, Rachita Mishra, Chinmaya Swarup Pattanaik, Himansu Sekhar Rout (Archives of Current Research International, 2025)
Climate stress conditions such as drought, heat, salinity, and erratic rainfall patterns have become significant barriers to sustainable fruit production. To maintain and improve fruit yields under such stressors, a combination of agronomic interventions and plant physiological approaches is essential. This review synthesizes the latest research on how agronomic practices—such as mulching, drip irrigation, nutrient management, and intercropping—when integrated with physiological strategies like stress-tolerant cultivars, hormonal priming, and antioxidant regulation, can enhance fruit yield resilience. Emphasis is laid on integrated approaches and case studies from tropical and sub-tropical fruit crops.